2018
DOI: 10.4172/2161-1025.1000199
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Antimalarial Drug Mefloquine for Cancer Treatment

Abstract: Mefloquine (MQ) is a quinoline class of drugs that has been in clinical use for the last four decades for the prophylaxis and treatment of malaria. Several recent literature studies on MQ illustrate that this drug exhibits good to excellent cytotoxicity and cell proliferation inhibition against several cancer cells. MQ also exhibits good in vivo tumor growth inhibition as a single agent and effectively synergizes with primary cancer chemotherapeutics in arresting tumor growth. Mechanism of action studies indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…24 Among various aminoquinoline-antimalarials, cancer celldirected cytotoxicity of MQ is well documented, involving numerous tentative molecular mechanisms, including autophagic-lysosomal blockade, inhibition of P-glycoprotein-dependent drug efflux, NFκB pathway attenuation through IKK inactivation, and induction of redox dysregulation. [46][47][48][49] Here we demonstrate for the first time that MQ induces cell death in cultured malignant melanoma cells displaying apoptogenic activity observable even in BRAFi-resistant BRAF V600E /NRAS Q61K A375 melanoma cells (Figures 1 and 4), an effect associated with rapid induction of proteotoxic and oxidative stress response gene expression (Figure 2).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…24 Among various aminoquinoline-antimalarials, cancer celldirected cytotoxicity of MQ is well documented, involving numerous tentative molecular mechanisms, including autophagic-lysosomal blockade, inhibition of P-glycoprotein-dependent drug efflux, NFκB pathway attenuation through IKK inactivation, and induction of redox dysregulation. [46][47][48][49] Here we demonstrate for the first time that MQ induces cell death in cultured malignant melanoma cells displaying apoptogenic activity observable even in BRAFi-resistant BRAF V600E /NRAS Q61K A375 melanoma cells (Figures 1 and 4), an effect associated with rapid induction of proteotoxic and oxidative stress response gene expression (Figure 2).…”
Section: Discussionmentioning
confidence: 61%
“…Repurposing of clinical antimalarials has shown promise for cancer‐directed molecular intervention, and inhibitory modulation of autophagic‐lysosomal function has been substantiated as a major molecular mechanism of action underlying cancer cell‐directed activity of antimalarials 24 . Among various aminoquinoline‐antimalarials, cancer cell‐directed cytotoxicity of MQ is well documented, involving numerous tentative molecular mechanisms, including autophagic‐lysosomal blockade, inhibition of P‐glycoprotein‐dependent drug efflux, NFκB pathway attenuation through IKK inactivation, and induction of redox dysregulation 46–49 …”
Section: Discussionmentioning
confidence: 99%
“…Mefloquine is an antimalarial compound with anticancer potential [ 60 ]. A previous experimental study has shown that mefloquine at 20 µM selectively and completely abolished the cell proliferation of two human PCa cell lines DU145 and PC3, by hyperpolarization of mitochondrial membrane potential and increased production of ROS resulting in rapid cancer cell death through inhibition of Akt phosphorylation and activated JNK, ERK and AMPK signaling [ 60 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of cell viability at compound 5 (Mefloquine Hydrochloride, MH) concentrations around sevenfold lower than those observed in the aggregate refolding assays, most likely indicates that the effect of this drug could be due to a mechanism different from chaperone inhibition. Indeed, it has been reported that similar MH concentrations exert antiproliferative effects through an increased lysosomal biogenesis and activation, followed by oxidative stress, lysosomal lipid damage and functional impairment [80].…”
Section: Discussionmentioning
confidence: 99%